Simultaneous localization and mapping : exactly sparse information filters - 527823 Wang, Zhan; Huang, Shoudong, 1969-; Dissanayake, Gamini (Singapore ; Hackensack, NJ. : World Scientific)
Includes bibliographical references (p. 180-194)